Dukungan Keluarga terhadap Kepatuhan Minum Obat pada Penderita Tuberculosis dengan Multidrug Resistant (TB-MDR) - Laina Noviana; Siti Zahara Nasution; Arlinda Sari Wahyuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship of family support to medication adherence in MDR-TB patients. This research method is descriptive correlation with cross sectional research design. The research sampling technique is total sampling. The results showed that adherence to taking medication in MDR-TB patients was more commonly found in good family support, namely as many as 23 respondents (92.6%), the results of the chi-square test obtained a p-value = 0.000 meaning there was a relationship between family support medication adherence in MDR-TB patients. In conclusion, there is a relationship between family support and medication adherence in MDR TB patients. Keywords: Family Support, Medication Compliance, MDR-TB.